The Effectiveness of Warm Compresses in Reducing Dysmenorrhea Pain Among Adolescent Girls: A Pre-Experimental Study in Bengkulu, Indonesia - Umami, Desi Aulia (Utan Kayu Publishing, 2022)
This study examines the effectiveness of warm compresses in reducing dysmenorrhea pain among adolescent girls. A pre-experimental one-group pre-post test design was used. The study was conducted at the Youth Posyandu in Tanjung Sanai I Rejang Lebong Village, Bengkulu, Indonesia, from June 6 to June 30, 2023. A total of 24 participants were selected using convenience sampling. Data were collected through a structured questionnaire and a standardized pain scale, validated through a pilot test. Pain levels were measured before and after applying warm compresses to the lower abdomen for 15-20 minutes, three times daily. Before the intervention, 54.2% of participants reported moderate pain, and 33.3% reported severe pain. After applying warm compresses, 50% of participants reported no pain, 29.2% reported mild pain, 16.7% reported moderate pain, and only 4.2% reported severe pain. The reduction in pain levels was statistically significant (p=0.000). Warm compresses significantly reduce dysmenorrhea pain in adolescent girls, shifting pain levels from moderate and severe to mild or none. This method is practical, accessible, and effective, offering a valuable non-pharmacological option for managing menstrual pain in young women. Abstrak: Studi ini mengkaji efektivitas kompres hangat dalam mengurangi nyeri dismenore pada remaja putri. Penelitian ini menggunakan desain pra-eksperimental dengan pre-post test satu kelompok. Penelitian dilakukan di Posyandu Remaja Desa Tanjung Sanai I Rejang Lebong, Bengkulu, Indonesia, dari 6 hingga 30 Juni 2023. Sebanyak 24 partisipan dipilih menggunakan teknik sampling kemudahan. Data dikumpulkan melalui kuesioner terstruktur dan skala nyeri standar, divalidasi melalui uji coba. Tingkat nyeri diukur sebelum dan sesudah penerapan kompres hangat di perut bagian bawah selama 15-20 menit, tiga kali sehari. Sebelum intervensi, 54,2% partisipan melaporkan nyeri sedang, dan 33,3% melaporkan nyeri parah. Setelah penerapan kompres hangat, 50% partisipan melaporkan tidak ada nyeri, 29,2% melaporkan nyeri ringan, 16,7% melaporkan nyeri sedang, dan hanya 4,2% melaporkan nyeri parah. Penurunan tingkat nyeri ini signifikan secara statistik (p=0,000). Kompres hangat secara signifikan mengurangi nyeri dismenore pada remaja putri, mengubah tingkat nyeri dari sedang dan parah menjadi ringan atau tidak ada. Metode ini praktis, mudah diakses, dan efektif, menawarkan pilihan non-farmakologis yang berharga untuk mengelola nyeri menstruasi pada wanita muda.